Kajian risiko usaha tani padi di Indonesia - Marten Umbu Kaleka; Elita Maulida; Egidius Taek; I Putu Edi Swastawan; Gede Mekse Korri Arisena (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Rice is one of the food crop commodities that plays an important role in meeting the primary needs of the Indonesian people. The high demand for rice can be seen from the increase in the amount of public consumption of these commodities. The basic method used in this research is the literature study method and the library method. The results showed that factors affecting the production of rice farming in Indonesia with various conditions were land area, fertilizer costs, pesticides, labor, seeds / seeds, age, capital; and counseling. The dominant influencing factor is land area factor. In general, things that are most likely to become production risks are natural disasters, weather and climate, pests, topology, and capital. It is known that there are differences in the risk of rice production between cropping patterns. The risk of rice farming can also be seen from an income perspective, one of the variables that has a significant positive effect on the risk of rice farming income is land area. For the two main stakeholders (farmers and insurance companies), the level of risk is also the basis for the implementation of AUTP. Risk management of rice farming must be adjusted based on a risk perspective. In the internal aspect, risks can be anticipated through increasing the capacity of farmers. On the external aspect, risks are still possible to be overcome through AUTP. The government can take a role in the aspect of capacity building for farmers and optimizing the downstreaming of the AUTP program so that it is right on target.